(CaO‐Y2O3)@LiFe5O8 magnetic catalyst by doping yttrium for improving stability: Optimized by response surface methodology for biodiesel production. Issue 5 (19th November 2019) - Chen, Xuan; Yue, Chengguang; Zhang, Pingbo; Fan, Mingming; Jiang, Pingping
Abstract: In this work, CaO@LiFe5 O8 and (CaO‐Y2 O3 )@LiFe5 O8 solid base catalysts were synthesized using LiFe5 O8 as the magnetic core to support the active centers. The as‐prepared catalysts and commercial CaO were characterized using X‐ray diffraction, scanning electronic microscope, and CO2 ‐temperature‐programmed desorption techniques. The results indicated that CaO@LiFe5 O8 and (CaO‐Y2 O3 )@LiFe5 O8 solid base catalysts, which could be recycled under the external magnetic field because of their strong magnetism, exhibited better dispersibility and higher total number of basic sites compared with commercial CaO. Additional water and oleic acid were added to the reaction system of palm oil with methanol, and the catalyst was exposed to air to detect its stability in the reaction process. The experiments showed that the (CaO‐Y2 O3 )@LiFe5 O8 solid base catalyst performed better and possessed not only good water resistance ability but also preferable tolerance to air exposure. In addition, response surface methodology based on the Box–Behnken design was used to optimize the process parameters for the synthesis of biodiesel from palm oil and methanol in the presence of (CaO‐Y2 O3 )@LiFe5 O8 . The optimum process conditions were determined as follows: reaction temperature was 64.96°C, reaction time 4.36 hr, methanol: oil 13, catalyst amount 3.73%, and the highest biodiesel yield reached 96.21%. Abstract : Two magnetic calcium‐based solid base catalysts exhibited excellent catalytic activity and stability for the synthesis of biodiesel from palm oil and methanol. With magnetism, two magnetic calcium‐based solid base catalysts were easily recovered. Moreover, the optimal process parameters for biodiesel production were determined by response surface methodology based on the Box–Behnken design, and the highest biodiesel yield was 96.21%.